Kualitas kimia dan organoleptik nugget ikan gabus melalui penambahan tepung kacang merah - Leni Anggraini; Andriani Andriani (Politeknik Kesehatan Kemenkes Aceh, 2020)
Background: The addition of red bean flour is an alternative to increase protein content. Red bean nuggets also still have low protein content, it is necessary to add protein from animal sources. One of the high protein fish is snakehead fish which reaches 25.1% while 6.224% of the protein is in the form of albumin in synergy with the mineral Zn.Objective: The research objective was to measure the effect of adding red bean flour to the organoleptic test (color, texture, aroma, taste) of snakehead fish nuggets.Methods: Experimental research with a completely randomized design (CRD). Organoleptic tests at the Food Technology Laboratory of the Aceh Health Polytechnic Nutrition Department and chemical tests at the Food Analysis Laboratory of the Faculty of Agriculture, Syiah Kuala University and the Syah Kuala University Integrated Laboratory in March 2019, descriptive univariate analysis including frequency and percentage distribution, bivariate test with ANOVA test and Duncan's continued test.Results: The results of the analysis of variance (ANOVA) showed that the addition of red bean flour had a significant effect on organoleptic snakehead fish nuggets (p <0.05). Chemical test results, the highest protein content in treatment 50 grams (FA) = 11.93, the highest crude fiber content in treatment 50 grams (FA) = 2.52, the highest crude fat content in treatment 75 grams (FB) = 15.63, the highest ash content in treatment 100 grams (FC) = 2.04, the highest water content in treatment 50 grams (FA) = 45.63 and the highest carbohydrate content in treatment 50 grams (FC) = 32.05.Conclusion: The addition of red bean flour had a significant effect on the organoleptic snakehead fish nuggets. The highest levels of protein and carbohydrates and fiber content in snakehead fish nuggets was higher in the 50 gram (FA).